(untitled) (Studia austriaca, 2012)
The following essay explores the theme of remembrance as a question of identity in Doron Rabinovici’s novel Suche nach M. The Austria Jewish author concentrates on the quest for self-determination through various means, which are determined by generational differences. While the generation of survivors sees remembrance of the Holocaust as a moment of silence, their children commemorate it through masquerades or carnivals. Rabinovici’s novel, with its emphasis on a collective search for identity, is an exemplary contribution to Holocaust literature as a re-elaboration of Jewish cultural biblical tradition.